Passive-dynamic ankle-foot orthosis improves medium-term clinical outcomes after severe lower extremity trauma. Issue 5 (9th November 2018) - Ladlow, Peter; Bennett, N; Phillip, R; Dharm-Datta, S; McMenemy, L; Bennett, A N
Abstract : Introduction: Individuals with delayed below-knee amputation have previously reported superior clinical outcomes compared with lower limb reconstruction. The UK military have since introduced a passive-dynamic ankle-foot orthosis (PDAFO) into its rehabilitation care pathway to improve limb salvage outcomes. The aims were to determine if wearing a PDAFO improves medium-term clinical outcomes and what influence does multidisciplinary team (MDT) rehabilitation have after PDAFO fitting? Also, what longitudinal changes in clinical outcomes occur with MDT rehabilitation and how do these results compare with patients with previous lower extremity trauma discharged prior to PDAFO availability? Methods: We retrospectively evaluated levels of mobility, activities of daily living, anxiety, depression and pain in a heterogeneous group of 23 injured UK servicemen 34±11 months after PDAFO provision. We also retrospectively analysed 16 patients across four time points (pre-PDAFO provision, first, second and final inpatient admissions post-PDAFO provision) using identical outcome measures, plus the 6 min walk test. Results: Outcomes were compared with previous below-knee limb salvage and amputees. Before PDAFO, 74% were able to walk and 4% were able to run independently. At follow-up, this increased to 91% and 57%, respectively. Mean depression and anxiety scores remained stable over time (p>0.05). After 3 weeks, all patients could walk independently (pre-PDAFO=31%). Mean 6 min walk distance significantly increased from 440±75 m (pre-PDAFO) to 533±68 m at last admission (p=0.003). The ability to run increased from 6% to 44% after one admission. Conclusions: All functional and most psychosocial outcomes in PDAFO users were superior to previous limb salvage and comparable to previous below-knee amputees. The PDAFO facilitated favourable short-term and medium-term changes in all clinical outcome measurements.